Rekonstruksi Tanggung Jawab Hukum Platform Digital Dalam Transaksi Agribisnis Berbasis Keadilan Substantif di Indonesia - Gayatri, Annisa; Fahamsyah, Ermanto; Adiwibowo, Yusuf (Universitas Pancasakti Tegal, 2026)
The rapid development of digital platforms in the agribusiness sector has transformed transactional relationships among farmers, digital platforms, and consumers. However, this development has not been accompanied by adequate legal regulations ensuring legal certainty and protection for farmers as the weaker party. This study aims to analyze the legal framework governing the liability of digital platforms in agribusiness transactions in Indonesia and to formulate a reconstruction of such liability based on substantive justice. This study employs a normative juridical method using statutory, conceptual, and case approaches. The findings reveal that Article 19 of Law Number 8 of 1999 concerning Consumer Protection and Article 15 of Law Number 11 of 2008, as lastly amended by Law Number 1 of 2024 concerning Electronic Information and Transactions, do not explicitly regulate the legal status and liability of digital platforms in agribusiness transactions. This regulatory gap creates legal uncertainty, particularly when digital platforms rely on standard contract clauses to limit their liability, as reflected in the TaniHub Group case. This study concludes that the legal liability of digital platforms should be reconstructed by recognizing platforms as active legal subjects directly responsible under the principle of substantive justice to ensure stronger legal protection for farmers.